Energy expenditure and body composition changes after an isocaloric ketogenic diet in overweight and obese men: A secondary analysis of energy expenditure and physical activity - Friedman, Mark I. (PLoS One, 2019)
BACKGROUND: A previously published pilot study assessed energy expenditure (EE) of participants with overweight and obesity after they were switched from a baseline high-carbohydrate diet (BD) to an isocaloric low-carbohydrate ketogenic diet (KD). EE measured using metabolic chambers increased transiently by what was considered a relatively small extent after the switch to the KD, whereas EE measured using doubly labeled water (EE(DLW)) increased to a greater degree after the response in the chambers had waned. Using a publicly available dataset, we examined the effect of housing conditions on the magnitude of the increase in EE(DLW) after the switch to the KD and the role of physical activity in that response. METHODS: The 14-day EE(DLW) measurement period included 4 days when subjects were confined to chambers instead of living in wards. To determine the effect on EE(DLW) only for the days subjects were living in the wards, we calculated non-chamber EE (EE(nonchamber)). To assess the role of physical activity in the response to the KD, we analyzed chamber and non-chamber accelerometer data for the BD and KD EE(DLW) measurement periods. RESULTS: In comparison with the increase in average 14-day EE(DLW) of 151 kcal/d ± 63 (P = 0.03) after the switch to the KD, EE(nonchamber) increased by 203 ± 89 kcal/d (P = 0.04) or 283 ± 116 kcal/d (P = 0.03) depending on the analytical approach. Hip accelerometer counts decreased significantly (P = 0.01) after the switch to the KD, whereas wrist and ankle accelerometer counts did not change. CONCLUSIONS: Switching from the BD to the KD substantially increased EE(DLW,) but apparently only on days subjects were living in the ward outside the metabolic chamber. Increased physical activity as measured by accelerometry did not appear to account for this effect.